قيم الهوية في المدرسة الابتدائية الجزائرية بين الإصلاحات التربوية للجيل الأول والثاني - بن عمار, أشواق (Universty of Eloued جامعة الشهيد حمه لخضر, 2021)
الملخص: حاولت هذه الدراسة تسليط الضوء على قيم الهوية في المدرسة الابتدائية الجزائرية بين الإصلاحات التربوية للجيل الأول والثاني(دراسة تحليلية مقارنة لمحتوى كتب المواد الاجتماعية للسنة الثالثة من التعليم الابتدائي)، وقد هدفت هذه الدراسة إلى تحليل المحتوى كتب المواد الاجتماعية والمتمثلة في كتاب التربية المدنية وكتاب التربية الإسلامية وكتاب التاريخ للسنة الثالثة من التعليم الابتدائي في ظل إصلاحات التربوية للجيل الأول والثاني، ومقارنة بين التحليلين والكشف عنما تحمله من قيم تساعد على ترسيخ وغرس مقومات الهوية الوطنية من حيث أبعادها الدينية، والوطنية والأمازيغية والثقافية في نفوس الأفراد ومعرفة حقوقهم وواجباتهم اتجاه مجتمعهم، ليكون الفرد منسجما ومنتمي المجتمعة وقادرا على المشاركة الإيجابية والفاعلة داخله. واعتمدت الدراسة على المنهج الوصفي والمنهج المقارن باستخدام تقنية تحليل المحتوى، حيث تم تحليل محتوى كتب المواد الاجتماعية (التربية الإسلامية- التربية المدنية- التاريخ) للجيل الأول والجيل الثاني لسنة الثالثة من التعليم الابتدائي في المدرسة الجزائرية، معتمدين في ذلك على شبكة التحليل محتوى تضمنتأبعاد الهوية:بعد الدين الإسلامي، بعد العروبة،البعد الامازيغي، البعد الوطني، التي تمثل فئات التحليل.وتم الاعتماد على وحدة الفكرة كوحدة لتحليل في الدراسة الحالية على اعتبار أنها من أهم وحدات تحليل المضمون وابسطها استخداما في عملية التحليل والترميز. وقد توصلت هذه الدراسة إلى جملة من النتائج تمثلت في مايلي: - أعطت الإصلاحات التربوية للجيل الأول والجيل الثاني أهمية للبعد الإسلامي كأحد عناصر الهوية الوطنية باعتباره ثقافة وحضارة وأساس الوحدة الوطنية للمجتمع الجزائري، كما أن الدين الإسلامي هو نظام وتنظيم اعتقادي واجتماعي، يكفل اتحاد وثبات واستقرار المجتمع الجزائري من خلال تعزيز دور ومكانة التربية، في مناهج التربية الإسلامية. - اهتمت الإصلاحات التربوية للجيل الأول والجيل الثاني بتعزيز مكانة اللغة العربية باعتبارها احد المكونات الثابتة للهوية الوطنية في الجزائر، وكمادة دراسية وكلغة تعليم وتعلم في جميع مراحل التعليم الدراسية. - أولت هذه الإصلاحات اللغة الامازيغية كمركب من مركبات الهوية الوطنية والثقافية الجزائرية، اهتماما ضمن مبادئها وغاياتها التربوية والتعليمية، وذلك بضرورة تعليم اللغة الامازيغية كجزء من التراث الثقافي للمجتمع الجزائري، خاصة في إصلاحات مناهج الجيل الثاني التي أعطت للبعد الامازيغي مكانا بارزا في مناهجها خاصة منهاج التربية المدنية. - كما اهتمت الإصلاحات التربوية للجيل الأول والثاني بالبعد الوطني من خلال تعزيز وإرساء دعائم التاريخ الوطني للمتعلم عن طريق تحسيسه بالعناصر الأساسية التي تشكل محيطه والعلاقات التي تربط بعضها ببعض وما ينتج عنها من تفاعلات، من خلال بناء الحاسة التاريخية، والانتماء الحضاري والثقافة المحلية، ويكتشف أهم مكون من مكونات هويته الوطنية، والشعور بالبعد الوطني. Abstract: This study attempted to shed light on the values of identity in the Algerian elementary school between the educational reforms of the first and second generations (a comparative analysis of the content of books of social materials for the third year of primary education). This study aimed to analyze the content of books of social materials, represented in the civics book and the education book Islamic history book for the third year of primary education in light of the educational reforms of the first and second generation, and a comparison between the two analyzes and the disclosure of the values they bear in order to establish and implant the foundations of the national identity in terms of its religious, national, Amazigh and cultural dimensions in the souls of individuals and to know their rights and duties towards their society, so that The individual is harmonious and belonging to a community and is able to participate positively and actively within it. The study relied on the descriptive approach and the comparative approach using the content analysis technique, where the content of social material books (Islamic education - civic education - history) was analyzed for the first generation and the second generation of the third year of primary education in the Algerian school, relying on this on the content analysis network that included dimensions Identity: the dimension of the Islamic religion, after Arabism, the Amazigh dimension, the national dimension, which represent the categories of analysis. The idea unit was relied upon as a unit of analysis in the current study, considering that it is one of the most important units of content analysis and the simplest used in the process of analysis and coding. This study reached a set of results as follows: - The educational reforms of the first and second generation have given importance to the Islamic dimension as one of the elements of the national identity as it is a culture, civilization and the basis of the national unity of Algerian society, just as the Islamic religion is a belief and social organization and organization that guarantees the union, stability and stability of Algerian society by strengthening the role and position of education, in educational curricula Islamic. - The educational reforms of the first and second generation focused on strengthening the position of the Arabic language as one of the fixed components of the national identity in Algeria, as a subject and as a language of instruction and learning in all educational stages. - These reforms have given the Amazigh language as a component of the Algerian national and cultural identity, attention within its pedagogical and educational principles and objectives, with the need to teach the Amazigh language as part of the cultural heritage of Algerian society, especially in the reforms of the second generation curricula that gave the Amazigh dimension a prominent place in its curricula, especially the Civic Education Curriculum. - The educational reforms of the first and second generations also paid attention to the national dimension by strengthening and laying the foundations of the national history of the learner by sensitizing him to the basic elements that form his surroundings, the relationships that bind each other and the resulting interactions, through building the historical sense, civilization and local culture, and discovering the most important It is a component of his national identity, and a sense of the national dimension.
دراسة تحليلية مقارنة لمحتوى كتب المواد الاجتماعية للسنة الثالثة من التعليم الابتدائي
أطروحة دكتوراه تخصص علم الّإجتماع في العلوم الإجتماعية
Keywords: الهوية- قيم الهوية الوطنية- التعليم الابتدائي- الإصلاحات التربية للجيل الأول- الإصلاحات التربية للجيل الثاني; Identity - National Identity Values - Primary Education - Education Reforms for the First Generation - Education Reforms for the Second Generation.